Risk-taking in social settings: Group and peer effects - Spiros Bougheas; Jeroen Nieboer; Martin Sefton (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2013)
We investigate experimentally the effect of consultation (unincentivized advice) on choices under risk in an incentivized investment task. We compare consultation to two benchmark treatments: one with isolated individual choices, and a second with group choice after communication. Our benchmark treatments replicate findings that groups take more risk than individuals in the investment task; content analysis of group discussions reveals that higher risktaking in groups is positively correlated with mentions of expected value. In our consultation treatments, we find evidence of peer effects: decisions within the peer group are significantly correlated. However, average risk-taking after consultation is not significantly different from isolated individual choices. We also find that risk-taking after consultation is not affected by adding a feedback stage in which subjects see the choices of their consultation peers.
Keywords: C91; C92; D71; D80; 330; experimental economics; choice under risk; advice; social influence; peer effects